2022
DOI: 10.1002/ppap.202100209
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature reduction of SnO2by floating wire‐assisted medium‐pressure H2/Ar plasma

Abstract: Reduction of SnO 2 to form spherical Sn particles and Sn etching are obtained by floating wire (FW)-assisted medium-pressure H 2 /Ar plasma. High-density H 2 /Ar plasma (10 14 cm −3 ) with a larger treatment area at medium pressure (10 kPa) produces a two-times higher removal rate of SnO 2 (0.111 mg/min) than that at atmospheric pressure with the same treatment area of 300 mm 2 . SnO 2 film is removed from the glass surface by a two-step process involving (1) reduc-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Atmospheric pressure plasma (APP) and medium-pressure plasma techniques with a large difference in chemical kinetics compared to low-pressure plasma are able to miniaturize equipment size, fabrication cost, and energy consumption 11 17 . Medium-pressure plasma (0.2–50 kPa) can produce higher plasma density compared to vacuum plasma and larger plasma volume compared to APP 18 20 . In order to improve the plasma density at a remote region where the substrate is placed, we have inserted a long floating metal wire inside the discharge tube to enhance the electric field not only near the copper coil region, but also at a remote region.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure plasma (APP) and medium-pressure plasma techniques with a large difference in chemical kinetics compared to low-pressure plasma are able to miniaturize equipment size, fabrication cost, and energy consumption 11 17 . Medium-pressure plasma (0.2–50 kPa) can produce higher plasma density compared to vacuum plasma and larger plasma volume compared to APP 18 20 . In order to improve the plasma density at a remote region where the substrate is placed, we have inserted a long floating metal wire inside the discharge tube to enhance the electric field not only near the copper coil region, but also at a remote region.…”
Section: Introductionmentioning
confidence: 99%
“…26) It is also reported that H 2 plasma treatment of a SnO 2 substrate produces spherical Sn droplets on the surface. 27,28) Therefore, there is a possibility that the Ga droplets shown in Fig. 3 were formed not from Ga hydrides but by the removal of nitrogen by the reaction of hydrogen radicals, leaving Ga on the surface.…”
mentioning
confidence: 99%